Taxonomy Of Spiritual Quotient Learning Outcomes: an Insight From Tasawwuf Perspective - Moh. Muslih; Muhamad Rifa'i Subhi (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The spiritual quotient (SQ) has a vital role in humans because it serves as the foundation of other intelligence. This study aims to present new insight on the taxonomy of the SQ learning outcomes for students, namely from the tasawwuf perspective. Using a qualitative meta-synthesis approach to explore various sources related to the taxonomy of the SQ learning outcomes through interpretative process, the study found that, in general, the SQ helps a person develop into a complete human being through the inclusion of the sense of worship in every action and thought. The taxonomy of the SQ learning outcomes includes the dimensions of taubat, wara’, zuhud, tawakal, zikr, khalwat, ikhlas, and ridla. If implemented in Islamic education, the said taxonomy will help students know their God, prioritize their conscience to solve problems in life and the learning activity, live life more meaningfully, and be motivated to benefit themselves and others in their learning process. Taken together, these findings strengthen the view that the spiritual quotient can make other intelligence function more optimally.